Implementation Issues and Challenges in Applying Lean Manufacturing Tools & Techniques in Different Manufacturing Environments - Low, Kwee Ang (2005)
Lean Manufacturing has made a significant impact on both the academic and manufacturing circles in the last decade. Fostered by a rapid spread into many other industrial sectors beyond the automotive industry, there has been significant development and "localisation" of the Lean Manufacturing concept in both developed and developing countries worldwide. Despite its successful application in a wide range of industries, little research has been carried out on its successful application outside the traditional high-volume, or massproduction manufacturing environment. It has been found that there is a lack of relevant literature on the application in the high-variety manufacturing milieu. In this aspect, this research objective is to determine: 1) The implementation issues when applying Lean Manufacturing tools and techniques in high-variety manufacturing environment, and 2) Are there any challenges encountered in applying these Lean Manufacturing tools and techniques in the high-variety manufacturing environment. This research will focus on two plants, with different manufacturing scenes, one a high-volume mass-production plant and the other a high-variety manufacturing plant in implementing the Lean Manufacturing tools and techniques. This paper starts with the background and the key defining concept of Lean Manufacturing followed by a review of the various Lean Manufacturing tools and techniques available. This is followed by the identification of the issues and challenges encountered by the two manufacturing plants during the implementation. The research concludes by providing a framework for the successful implementation of Lean Manufacturing tools and techniques in a high-variety manufacturing environment and future research recommendations. A qualitative research method was adopted to analyse the data. An open-ended questionnaire was designed, and the findings incorporated into the semi-structured interviews with the Lean Champions and the Plant Managers. The shop floors of both manufacturing plants were visited and observed after the interviews had confirmed actual Lean Manufacturing implementations. A summary copy of the researcher’s findings was sent to the Lean Champions for verification before concluding this research. The research results indicate that there were many unique issues and challenges in applying Lean Manufacturing tools and techniques in a high-variety manufacturing environment. Despite the many issues and challenges, Lean manufacturing can in fact be applied to high-variety manufacturing environment but with much difficulty. The implementation journey is without doubt challenging, but with perseverance and an enthusiastic leadership team, it can be successful.